Expanding grasslands? Structural biome shifts in the dryland rangelands of the eastern Karoo revealed through long-term observation of climate, vegetation and land use change - Arena, Gina (Department of Biological Sciences, 2022)
Biome shifts caused by climate and land use change threaten global dryland ecosystems and the provision of services needed to sustain human livelihoods. The overarching drivers of early 20th century dryland degradation in South Africa have been attributed to high stocking rates and overgrazing by domestic livestock. Predictions of an eastward encroachment of shrublands into the semiarid grasslands, and resultant declines in productivity, emerged in the 1950s based on concerns that livestock overgrazing would persist. In response to these concerns, appropriate research and government interventions were implemented to address rangeland and livestock mismanagement. However, the role of long-term climate as a driver of semiarid vegetation change was poorly understood, particularly for changes occurring at the interface of the NamaKaroo and Grassland biomes where shrubland encroachment could be detected along a gradient of increasing annual rainfall. It is this gradient that controls the natural biome transition from shrub-dominance to grass-dominance. However, the prediction of shrubland encroachment was refuted when research in the early 1990s revealed that the vegetation of this region (known as the ‘eastern Karoo') had undergone an increase in grass cover; a trend that persisted into the early 2000s. Questions around the influence of changing rainfall patterns on driving this increase in grassiness have since been investigated at a single location in the eastern Karoo. Findings indicated that an increase in annual rainfall drove the increase in grass cover, but the generality of this relationship across the broader rainfall gradient of the biome transition has not been examined. In addition to rainfall, grazing by domestic livestock has had a significant influence on the relative proportion of grasses and shrubs in the eastern Karoo. While other studies have alluded to changes in land use, few data have been presented and the relative influence of land use change has usually been under-estimated. The availability of historical data from past vegetation surveys, climate station records and magisterial district livestock censuses makes it possible to develop a more comprehensive synthesis of how vegetation has changed across the rainfall gradient in order to address questions around biome shifts. This thesis, therefore, aimed to determine whether a biome shift is related to a broader shift in the climate regime through the assessment of long-term vegetation change along the rainfall gradient, in relation to climate and land use change since the early 20th century. Annual and seasonal trend analysis was applied to monthly rainfall, temperature, pan evaporation, evapotranspiration and wind speed data. Trends indicated that 32% of sites in the eastern Karoo showed an increase in annual rainfall between 1874 and 2019, which was also defined by a significant shift to increasing early summer rainfall. A concomitant trend of decreasing annual, and late summer rainfall, was detected at 32% of sites located on the mesic end of the rainfall gradient. Monthly maximum temperature between 1971 and 2019 also increased by 1.0 °C at a rate of 0.04 ± 0.06 °Cy-1 and monthly minimum temperature decreased by 0.3 °C at a rate of -0.03 ± 0.11 °Cy-1 . Wind speed, an important driver of evaporative processes, decreased at 44% of sites since 1971 and decreasing trends in A-Pan evaporation were found at all sites. No discernible trends in evapotranspiration were detected. Declines in wind speed and evaporation were suggested to promote an increase in vegetation cover which may restore ecosystem processes and improve rangeland productivity. An analysis of multidecadal wet-dry phases in the climate record was also undertaken using the Standardised Precipitation Index. Through this, it was observed that the rainfall regime over the eastern Karoo is defined by three significant phases over the last century: an early wet phase (1886- 1902), a 70-year long dry phase (1902-1970), followed by the recent wet phase (1970-2014) that commenced with heavy rains in the mid-1970s across the summer rainfall region of southern Africa. Long-term changes in the cover and composition of plant species and growth forms were compared between 1962 and 2018 at 27 sites using the point intercept method. Changes in species composition were determined from Bray-Curtis similarity distances. The dominant growth forms were organised along a rainfall-edaphic gradient and plant communities were further defined by altitude. Hierarchical clustering of species cover per site recognised this underlying gradient. Thus, sites were categorised into three vegetation units: ‘Karoo', ‘Escarpment' and ‘Grassland'. Results showed that vegetation cover increased, and bare ground cover decreased, significantly at all but one site. Perennial grasses increased by 20%, 24% and 35% at Karoo, Escarpment and Grassland sites, respectively. Palatable dwarf shrubs increased by 15% at Karoo sites. These growth form changes translated to a broader-scale shift in the relative dominance of dwarf shrubs to grasses at 59% of sites in the Nama-Karoo biome, coinciding with the spatial pattern of increasing early summer rainfall and temperature. However, a multivariate analysis provided minimal evidence of species shifts between vegetation units or biomes, suggesting that compositional stability was maintained across the rainfall gradient. Percent changes in the cover of grasses and dwarf shrubs were analysed in relation to the climatic and edaphic parameters using multiple regression analysis, but no significant linear relationships were found. However, summer rainfall and temperature combined explained 26% of the variation in the percent change in grass cover. The effect of these changes on rangeland grazing capacity (ha/Large Stock Unit) was also evaluated using the ecological index method of the assessment of veld condition. There was a fivefold improvement in grazing capacity at Karoo sites and a twofold improvement at Escarpment and Grassland sites. Changes in the cover of grasses, dwarf shrubs and trees were additionally determined through fixed-point repeat photography at 85 sites on two different landforms, plains and hillslopes. A shift towards grass dominance relative to dwarf shrubs was estimated at 90% of sites located on the plains and at 100% of sites located on the hillslopes in the NamaKaroo. Variable trends were found at Grassland sites in both landforms. Tree cover remained unchanged in both biomes. Agricultural livestock census data at the magisterial district-level showed a fivefold decrease in sheep numbers between 1911 and 2017 while the number of cattle and equine animals remained largely unchanged. Goat numbers fluctuated over time in response to the demands for Angora mohair. Supporting perceptions of significant reductions in livestock numbers since the 1960s were conveyed by 18 local landowners as derived from semi-structured interviews. The introduction of conservation-friendly grazing systems, seasonal rainfall shifts, and increased drought frequency were also perceived as important drivers of vegetation change. However, a number of socio-ecological challenges, for example, livestock losses to theft, vermin, or fire, emerged as having significantly influenced management decisions. Therefore, the persistent structural shift in growth forms across the rainfall gradient since the 1960s has largely coincided with significant climatic shifts in rainfall and temperature. A secondary influence of long-term reductions in livestock numbers, and a change to conservation-friendly management practices, is suggested to have supported the recovery of vegetation, especially that of perennial grasses, and rangeland productivity.